2019
DOI: 10.1080/0305215x.2019.1639050
|View full text |Cite
|
Sign up to set email alerts
|

Metamodel-based multi-objective optimization of a turning process by using finite element simulation

Abstract: This study investigates the advantages and potentials of the metamodelbased multi-objective optimization (MOO) of a turning operation through the application of finite element simulations and evolutionary algorithms to a metal cutting process. The objectives are minimizing the interface temperature and tool wear depth obtained from FE simulations using DEFORM-2D software, and maximizing the material removal rate. Tool geometry and process parameters are considered as the input variables. Seven metamodelling me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Productivity was maximized, guaranteeing surface roughness values according to the ISO 7206-2 standard. The approach uses a new generation genetic algorithm design, in contrast to similar studies [5,19,20,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Productivity was maximized, guaranteeing surface roughness values according to the ISO 7206-2 standard. The approach uses a new generation genetic algorithm design, in contrast to similar studies [5,19,20,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, this singularity has received less attention compared to the other two regions of the wear curve [17,18]. At the same time, to evaluate this initial wear of the tool, it is necessary to apply multi-objective optimization [19] of the parameters of the cutting regime [20] in order to reduce its effects. To solve multi-objective optimization problems, a large number of tools have been developed [21].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we modified the implementation of the well-known (SPEA2), which has been previously used to optimise real-world engineering problems (Rezaei and Davoodi 2012;Amouzgar, Rashid, and Stromberg 2013;Tang et al 2016;Amouzgar et al 2018;Rao et al 2019;Amouzgar et al 2019). Figure 5 describes the SPEA2 process workflow.…”
Section: Proposed Modified Spea2 (M-spea2)mentioning
confidence: 99%
“…Hypervolume for minimisation of MOOP considered in this study with Nadir point as referenceAmouzgar et al (2019).…”
mentioning
confidence: 99%
“…It was concluded the surface roughness was significantly affected by cutting speed while the depth of cut had a predominant effect on the tool wear and feed rate significantly impacted the material removal rate. Amouzgar et al [9] simulated a turning operation using finite element method and then applied evolutionary algorithms to minimize the interface temperature and tool wear depth. They found that the metamodel-based method reduced the computational time by 70%.…”
Section: Introductionmentioning
confidence: 99%